A Review of Psychotropic drug prescription for patients with Intellectual disability at Alexandra Hospital (a specialist Intellectual Disability psychiatric hospital) outpatient clinic - Akpabio, Idorenyin Ubon (Department of Psychiatry and Mental Health, 2022)
Background: People with intellectual disability are more likely than the general population to be prescribed psychotropic agents. The most common indications include treatment of a psychiatric disorder and management of behaviours that challenge. Aim: The study aimed to assess the prescribing patterns of psychotropic medication to outpatients with intellectual disability at a psychiatric hospital. Setting: Alexandra hospital outpatient clinic, Cape Town. Methods: This was a retrospective folder and prescription chart review. Folders of all new patients (103) seen between January 2018 and August 2019 were examined at two points, the initial appointment and again at six months. The information was examined against the World Psychiatric Association (WPA) and the National Institute for Health and Care Excellence (NICE) guidelines for prescribing in people with intellectual disability. Results: psychotropic medication was prescribed to 88% of patients. Antipsychotics accounted for more than 56% of the medication prescribed and was used mainly to manage behaviours that challenge. Clinicians at Alexandra hospital followed prescribing guidelines to some extent; however, more still needs to be done to ensure best practice and care. Conclusion: This review revealed a few shortcomings in meeting prescribing guidelines by clinicians at Alexandra hospital. Measures to address these shortcomings could be the inclusion of medication review schedules and standardised forms for clerking and monitoring of side effects in patient files, the use of behavioural strategies as the primary management of behaviours that challenge, and the performance of regular clinical practice audits.